A concept of assertive courseware for hearing impaired learners - Abdul Mutalib, Ariffin; Ab Salam, Sobihatun Nur; Mahmuddin, Massudi; Ahmad, Mazida; Syed Yahya, Syarifah Nadia (Asian Research Publishing Network (ARPN), 2015)
This paper reports on an initiative that develops a concept of teaching and learning material for hearing-impaired learners in higher learning institutions.It describes the needs for the concept. The aim of the paper is to describe about the concept that is developed through User-centered Design approach.It involves observation and interview in three seminars in gathering the components of the concept.In the three seminars, users who are the hearing-impaired learners and their teachers were involved very closely.In the end, the concept has been derived and evaluated. The evaluation further reveal that the concept has been well-accepted by the users.